Silicon Nanotubes as Potential Therapeutic Platforms - Nguyen T. Le (Pharmaceutics, 2019)
Silicon nanotubes (SiNTs) with unique well-defined structural morphologies have been successfully fabricated and recognized as a novel architecture in the nanoscale Si family. While the typical dendritic microstructure of mesoporous silicon prepared anodically has been exploited previously for therapeutics and biosensing, our status of utilizing SiNTs in this regard is still in its infancy. In this review, we focus on the fundamental properties of such nanotubes relevant to therapeutic applications, beginning with a description of our ability to sensitively tune the structure of a given SiNT through synthetic control and the associated detailed in vitro dissolution behavior (reflecting biodegradability). Emphasis is also placed here on the range of functional moieties available to attach to the surface of SiNTs through a summary of current studies involving surface functionalization and strategies that facilitate conjugation with molecules of interest for multiple purposes, including cell labeling, nucleotide attachment, and scaffolding of therapeutic metallic nanoparticles. Experiments addressing our ability to load the interior of a given nanotube with species capable of providing magnetic field-assisted drug delivery are also briefly described. Given the range of diverse properties demonstrated to date, we believe the future to be quite promising for employing SiNTs as therapeutic platforms.